Pengaruh Pengembangan Kawasan Wisata Geopark Merangin Terhadap Kesejahteraan Masyarakat Desa Air Batu - Dinata, Indra Putra; Mussadun, Mussadun (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Geopark Merangin has enormous tourism potential in improving the local economy in Merangin. With its unique tourist attraction that is the geological heritage in the form of fossil flora and foliage which integrated with the natural conditions that are still beautiful as well as recreational sports rafting, so if it can be properly managed, will provide great benefit to the local economy. This potential has been seen by the local government, with the implementation of additional business development since 2011. The development is carried out in the form of infrastructure development, increased accessibility and promotion of the development center in Air Batu village. Along with the development of Geopark Merangin region, tourists began to arrive and have increased each year. Although there has been development of the area, but there are still people with low levels of prosperity. This study aims to assess the effect of tourism development for the welfare of society Geopark Merangin Air Batu village. To achieve the objectives of this study, the approach used is positivistic approach with quantitative methods and analysis techniques crosstab. From this study showed that the development of the area Geopark Merangin during the last 4 years has been an impact on economic conditions Air Batu village. The development of tourism has been able to improve the well-being, so that people who lower their welfare has decreased despite the decline is less significant.